Impact of Korea International Cooperation Agency (KOICA) Scholarship Programs on Capacity Building on Developing Countries - Khan, Shifadjzic; Yun, Byung Wook; Hwang, Hwa Seok (Journal of Ecohumanism, 2024)
The Korean International Cooperation Agency Scholarship Programs significantly contribute to the enhancement of human resource development in developing nations by offering individuals the chance to receive advanced education and professional training in South Korea. This paper provides a comprehensive review of the Korean International Cooperation Agency scholarship programs and their impact on capacity building in developing countries. Since its inauguration, Korean International Cooperation Agency has facilitated numerous scholarship opportunities for individuals from developing nations, focusing on fields such as public administration, healthcare, technology, agriculture, and environmental sustainability. Through these programs, Korean International Cooperation Agency has contributed to the empowerment of individuals, the strengthening of institutions, and the promotion of sustainable development in recipient countries. The review paper explores the objectives of Korean International Cooperation Agency scholarships and the long-term benefits on developing countries in terms of capacity building. Drawing from case studies, articles and program evaluations, this review highlights the role of these scholarships in fostering skilled leadership, enhancing local governance, and facilitating cross-cultural exchange. Ultimately, the paper underscores the importance of international cooperation and capacity building in accomplishing the United Nations’ Sustainable Development Goals (SDGs), particularly in education, economic growth, and global partnerships.